Analysis the Flexibility of ChatGPT Use in Chemistry Learning Among 12th Grade Students at Senior High School in Samarinda - Frederich Pakaenoni; Usman Usman; Agung Rahmadani; Sudjanani Ulfa; Kevin Tiurma Dame (Jambura Journal of Educational Chemistry, 2026)
The rapid development of artificial intelligence has influenced learning practices in chemistry, particularly through the use of ChatGPT as an adaptive learning tool. This study aims to explore how students interpret the flexibility of ChatGPT in supporting chemistry learning, focusing on flexibility of time, place, learning pace, interaction, and adaptation to individual needs. The study employed a qualitative research design with a phenomenological approach to capture students lived experiences in using ChatGPT during chemistry learning. Participants consisted of 122 twelfth grade students from SMAN 5 Samarinda and SMAK Sunodia Samarinda who actively used ChatGPT in their chemistry studies. Data were collected through open-ended questionnaires distributed via Google Forms. Data analysis followed the interactive qualitative analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing or verification. The findings reveal that students perceive ChatGPT as a flexible learning facilitator that allows learning anytime and anywhere, supports self paced learning, enables repeated explanation without pressure, and provides dialogic and responsive interaction tailored to individual understanding levels. ChatGPT also helps students regulate their learning, maintain learning continuity, and create a psychologically safe learning environment. Overall, ChatGPT is interpreted not as a replacement for teachers, but as a complementary learning support that enhances student independence, self-regulated, and conceptual understanding in chemistry. These results highlight the potential role of ChatGPT in supporting adaptive, personalized, and student centered chemistry learning.